Information technology adoption and its relationship with the business management in Small and Medium Enterprises (SME) - Lunardi, Guilherme Lerch; Dolci, Décio Bittencourt; Dolci, Pietro Cunha (Revista de Administração da UFSM, 2017)
It is widely recognized the importance of small and medium enterprises (SME) for a country to achieve and sustain their socioeconomic development. As the Information Technology (IT) acquisition becomes cheaper, more popular becomes its use in business. Thus, this article aims at better understanding the adoption of IT and its association with different management activities of SME. We conducted a survey with 4,341 SME located in Rio Grande do Sul, which respondents were the owners of their respective companies. The instrument assessed ten dimensions of business management: Planning, Customers, Work Team, Suppliers, Quality and Productivity, Point of Sale, Inventory, Sales, Credit, and Cash, as well as other categorical variables. The results show significant differences between computerized and not computerized companies, both in terms of profile and business management performance from companies that have adopted computers and Internet. In addition, the study showed a positive relationship between the amount of available computing resources in the company and the level of administrative activities.